THE UTILIZATION OF LOOSE PARTS MEDIA IN STEAM LEARNING FOR EARLY CHILDHOOD - Siti Wahyuningsih; Adriani Rahma Pudyaningtyas; Novita Eka Nurjanah; Nurul Kusuma Dewi; Ruli Hafidah; Muhammad Munif Syamsuddin; Vera Sholeha (Universitas Sebelas Maret, 2020)
STEAM-based learning (Science, Technology, Engineering, Arts, and Mathematics) has begun to be developed a lot recently. This learning is considered able to answer the challenges of the times to be able to develop learning in the 21st century. STEAM is not only developed for secondary to tertiary education but is also developed for learning in early childhood. The challenges for developing STEAM-based learning are not small. The teacher considers that to provide learning about technology, for example, one must use sophisticated computer-based learning media, so it requires expensive costs. Also, science and engineering learning has not been developed much in kindergarten (TK) learning because it is considered a difficult concept to understand and requires high costs for the learning media. Learning media for early childhood is diverse and does not have to all buy new materials at a high cost. Likewise with learning media that can be used to develop STEAM-based learning. Teachers can make use of items or materials that are easily available, such as rocks, tree branches, seeds, used bottle caps, dry leaves, clothespins, etc. These removable materials are called loose parts. Loose parts are loose objects that can be moved, manipulated, and how to use them is determined by the child. These removable materials as learning media can make children think creatively and imaginatively. Loose parts can also be used as media in STEAM learning.